Dry-particle glazed tile and preparation method thereof

By adjusting the base glaze and applying a medium glaze, the problem of air bubbles in dry-granule polished glazed tiles during the firing process was solved, improving the wear resistance and stain resistance of the tiles and enhancing their aesthetic value.

CN121005583APending Publication Date: 2025-11-25QINGYUAN GANI CERAMICS CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511169942.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-20
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

Existing dry-granule polished glazed tiles are prone to forming bubbles during the firing process, which leads to a decrease in the anti-fouling performance of the glaze and a reduction in mechanical strength, thus affecting their aesthetic value.

Method used

By adjusting the initial melting point and softening point of the base glaze, applying the first and second medium glazes, an exhaust channel is formed to prevent the formation of pores. Medium glazes are also applied before and after the inkjet printing layer to fix the transparent dry particles and ensure smooth exhaust.

Benefits of technology

It improves the transparency and color vibrancy of the glaze, enhances the wear resistance and stain resistance of the tiles, and improves their aesthetic value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a dry-particle glazed tile and a preparation method thereof, relates to the field of ceramic preparation, and aims to solve the problem that various properties of the tile are reduced due to glaze pores existing in the traditional dry-particle glazed tile by improving the preparation method and matching raw material formula and steps and process parameters. By adjusting the initial melting point and the softening point of the ground glaze, blocking is formed on the ground glaze layer, the blank layer is prevented from exhausting air to the glaze layer to form air holes, the exhaust problem of the blank layer is solved, the medium glaze is arranged on the upper portion and the lower portion of the second glaze layer respectively, an exhaust channel is formed, the exhaust problem of the second glaze layer is improved, and the air hole problem of the glaze surface is comprehensively improved. The invention further provides the dry-grain glazed tile, and the preparation scheme is adopted in the dry-grain glazed tile. In some preferable embodiments, pores in the glaze surface of the dry-particle glazed tile are not obvious, the wear resistance reaches 4-grade 2100 revolutions or above, the antifouling grade reaches 5-grade or above, and the glaze surface quality and various properties of the dry-particle glazed tile are obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of building ceramics, in particular to a dry particle glaze-finished tile and a preparation method thereof. BACKGROUND

[0002] The dry particle glaze-finished tile on the market at present is formed by applying a thick transparent dry particle on the body-bottom glaze-inkjet printed tile structure, and a thick transparent glass phase glaze layer is formed during the firing process, so as to improve the gloss and color brightness of the glaze-finished tile, and greatly improve the aesthetic value of the tile.

[0003] However, the prior art has the following disadvantages: 1. The transparent dry particle layer melts during the firing process, hinders the exhaust of the body, and causes small bubbles to exist in the glaze surface of the finished tile, which will be shown during the polishing process, forming glaze white spots.

[0004] 2. The glaze surface has many bubbles, which greatly reduces the stain resistance of the tile and reduces the stain resistance.

[0005] 3. The glaze surface has many bubbles, which affects the overall mechanical strength of the glaze layer and reduces the wear resistance. SUMMARY

[0006] The main purpose of the present application is to provide a preparation method of a dry particle glaze-finished tile, which improves the problem of glaze pores in the traditional dry particle glaze-finished tile, which reduces the performance of the tile.

[0007] To achieve the above purpose, the present application provides a preparation method of a dry particle glaze-finished tile, comprising the following steps: S1, preparing a body and drying the body to obtain a body layer; S2, applying a bottom glaze on the surface of the body layer, the initial melting point of the bottom glaze is 1068-1076℃, and the softening point is 1170-1178℃, to obtain a bottom glaze layer; S3, inkjet printing on the surface of the bottom glaze layer to obtain an inkjet printed layer; S4, spraying a first medium glaze on the surface of the inkjet printed layer to obtain a first glaze layer; S5, applying a transparent dry particle on the surface of the first glaze layer to obtain a second glaze layer; S6, spraying a second medium glaze on the surface of the second glaze layer to obtain a third glaze layer; S7, firing in a kiln, the firing temperature is 1185-1200℃, the firing period is 63.55-65.00min, and the surface of the tile is polished.

[0008] Preferably, in steps S4 / S6, the first medium glaze / second medium glaze is prepared by adding ceramic adhesive to adjust the glaze slurry specific gravity. In step S4, the first raw material is weighed according to the weight parts, and then glaze-forming auxiliary materials are added and ball-milled to obtain a first medium glaze with a specific gravity of 1.15±0.01g / ml. The first raw material includes, by weight parts: 195~205 parts of second glaze powder and 13~17 parts of alumina. The spraying amount of the first medium glaze is 190~200g / ml. 2 ; In step S6, the second raw material is weighed according to the weight parts, and then glaze-forming auxiliary materials are added and ball-milled to obtain a second medium glaze with a specific gravity of 1.05±0.01g / ml. The second raw material includes, by weight, 195~205 parts of second glaze powder, and the spraying amount of the second medium glaze is 160~170g / ml. 2 ; The chemical composition of the second glaze powder, by weight percentage, includes: SiO2 53.5~56.0%, Al2O3 11.5~13.0%, CaO 21~23%, MgO 1.0~2.0%, K2O 1.95~3.0%, Na2O 3.0~4.0%, with the balance being oxide impurities and / or loss on ignition, each with a weight percentage ≤0.5%. The glazing additives for the first and second medium glazes are composed of 0.7 to 0.9 parts by weight of methylcellulose, 0.5 to 0.7 parts by weight of sodium tripolyphosphate, and 95 to 105 parts by weight of water.

[0009] In this invention, the medium glaze refers to the glaze structure between the second glaze layer (i.e., the transparent dry granule layer) and the inner glaze layer. The ceramic adhesive in this invention refers to a binder with high-temperature stability; using ceramic adhesive to adjust the specific gravity of the glaze slurry can fix the transparent dry granules to the brick surface, preventing them from being blown away by the firing airflow during high-temperature firing in the kiln.

[0010] Commercially available dry-granule polished ceramic tiles are made by applying a thick layer of transparent dry granules to the body-base glaze-inkjet printed ceramic tile structure, forming a relatively thick transparent glass phase glaze layer during firing. However, this type of dry-granule polished ceramic tile suffers from poor transparency and numerous pores, leading to reduced wear resistance and stain resistance. This invention addresses this issue by adjusting the initial melting point and softening point of the base glaze, creating a barrier in the base glaze layer to prevent the body layer from releasing air into the glaze layer, thus preventing the formation of pores. This solves the air release problem in the body layer and helps reduce the porosity of the glaze surface. However, the issue of transparent dry granules still exists. To address the issue of pores formed by air venting in the granular glaze layer, this invention departs from the conventional method of directly applying transparent dry granules to the inkjet printing layer followed by firing. Instead, it applies a layer of medium glaze before and after the glass dry granule layer. The first medium glaze primarily assists in air venting from the transparent dry granules, remaining in an unsintered state while the granules melt, thus preserving the overall air venting channels of the glaze layer. The second medium glaze primarily binds the transparent dry granule layer, preventing it from being lifted away by the kiln's firing airflow. Together with the first medium glaze layer, it forms air venting channels, ensuring smooth air venting of the entire glaze layer. Furthermore, this invention further adjusts the formulation, specific gravity, and glaze application amount of the first and third glaze layers to promote air venting in the second glaze layer during firing, preventing pores in the second glaze layer (i.e., the transparent dry granule layer) and thus resolving its air venting problem.

[0011] In the preparation process of this dry-granule glazed tile, since the transparent dry granules are applied using a dry method and the amount applied is large, the preferred method for applying the medium glaze is spraying. Preferably, the first and second medium glazes are applied using a spray booth.

[0012] Further preferably, the second glaze powder has an initial melting point of 1095~1105℃ and a softening point of 1147~1157℃. The transparent dry granules have an initial melting point of 842~852℃ and a softening point of 1006~1016℃. The melting point of the second glaze powder is higher than that of the transparent dry granules within a certain range, which ensures that it is fully fired in the kiln environment and also ensures that it can form an exhaust channel in the transparent dry granule layer in conjunction with the first glaze layer.

[0013] Preferably, the chemical composition of the transparent dry granules, by mass percentage, includes: SiO2 56.5~57.7%, Al2O3 7.3~7.8%, CaO 11.5~13.0%, K2O 6.0~7.0%, BaO 3.0~4.0%, ZnO 10.5~12.0%, SrO 0.5~1.0%, with the balance being oxide impurities and / or loss on ignition, each with a weight percentage ≤0.5%. In step S5, 50~250 mesh transparent dry granules are applied using a dry granulator at a rate of 640~660 g / m³. 2 .

[0014] Preferably, the base glaze is prepared by ball milling the base glaze raw materials according to weight parts, adding glaze-forming auxiliary materials, and the base glaze raw materials according to weight parts include: 315-325 parts of first glaze powder and 45-48 parts of zirconium silicate. The glaze-forming auxiliary materials of the base glaze are composed of 0.7-0.9 parts of methylcellulose, 1.1-1.3 parts of sodium tripolyphosphate, and 150-160 parts of water according to weight parts; the glaze application rate of the base glaze is 360-380 g / m³. 2 The chemical composition of the first glaze powder, by weight percentage, includes: SiO2 58.5~63.0%, Al2O3 7.0~8.0%, CaO 7.0~8.0%, K2O 2.0~3.0%, Na2O 0.5~1.0%, ZrO2 15.5~17.0%, with the balance being oxide impurities and / or loss on ignition, each with a weight percentage ≤0.5%.

[0015] Preferably, the raw material chemical composition of the billet, by weight percentage, includes: SiO2 66.00~68.00%, Al2O3 19.50~21.00%, Fe2O3 0.50~0.65%, CaO 0.45~0.55%, MgO 0.8~1.0%, K2O 3.00~4.00%, Na2O 2.00~3.00%, with the balance being oxide impurities and / or loss on ignition, each with a weight percentage ≤0.5%.

[0016] This invention also proposes dry-granule polished glazed tiles, prepared by any of the aforementioned methods for preparing dry-granule polished glazed tiles. These tiles possess all the beneficial effects of the aforementioned preparation methods, which will not be elaborated upon here.

[0017] Unlike existing technologies, the beneficial effects of this invention are as follows: 1. By adjusting the initial melting point and softening point of the base glaze, a barrier is formed in the base glaze layer, preventing the body layer from venting into the glaze layer and forming pores; 2. By adjusting the formula, amount and specific gravity of the first and third glaze layers, the exhaust of the second glaze layer can be promoted during the firing process, thus preventing the formation of pores in the second glaze layer. 3. Because this method produces ceramic tile glaze with fewer vent holes, the finished product after polishing can achieve a stain resistance level of 5 and a wear resistance level of 4 at 2100 revolutions. 4. It solves the air release problem in the body layer and transparent dry granule layer, greatly improving the transparency of the tile surface and the vibrancy of the colors, thus greatly enhancing the aesthetic value of the tile. Detailed Implementation

[0018] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. In addition, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention.

[0019] This application provides a method for preparing dry-granulated glazed tiles, comprising the following steps: S1. Prepare a green body and dry the green body to obtain a green body layer; S2. Apply a base glaze to the surface of the body layer. The initial melting point of the base glaze is 1068~1076℃ and the softening point is 1170~1178℃ to obtain the base glaze layer. S3. Inkjet printing is performed on the surface of the base glaze layer to obtain an inkjet printed layer; S4. Spray the first medium glaze onto the surface of the inkjet printing layer to obtain the first glaze layer; S5. Apply transparent dry particles to the surface of the first glaze layer to obtain the second glaze layer; S6. Spray a second medium glaze onto the surface of the second glaze layer to obtain a third glaze layer; S7. Firing in a kiln at a temperature of 1185~1200℃ for a firing cycle of 63.55~65.00 min, followed by polishing of the tile surface.

[0020] The first and second medium glazes are applied using a spray gun.

[0021] In steps S4 / S6, the specific gravity of the first / second medium glaze is adjusted by adding ceramic adhesive. In step S4, the first raw material is weighed according to its weight proportions, and then glaze-forming auxiliary materials are added and ball-milled to obtain a first medium glaze with a specific gravity of 1.15±0.01 g / ml. The first raw material, according to its weight proportions, includes: 195~205 parts of second glaze powder and 13~17 parts of alumina. The spraying amount of the first medium glaze is 190~200 g / ml. 2 ; In step S6, the second raw material is weighed according to the weight parts, and then glaze-forming auxiliary materials are added and ball-milled to obtain a second medium glaze with a specific gravity of 1.05±0.01g / ml. The second raw material includes, by weight, 195~205 parts of second glaze powder, and the spraying amount of the second medium glaze is 160~170g / ml. 2The chemical composition of the second glaze powder, by weight percentage, includes: SiO2 53.5~56.0%, Al2O3 11.5~13.0%, CaO 21~23%, MgO 1.0~2.0%, K2O 1.95~3.0%, Na2O 3.0~4.0%, with the balance being oxide impurities and / or loss on ignition, each with a weight percentage ≤0.5%. The initial melting point of the second glaze powder is 1095~1105℃, and the softening point is 1147~1157℃. The glazing auxiliary materials for the first and second medium glazes, by weight, consist of 0.7~0.9 parts of methylcellulose, 0.5~0.7 parts of sodium tripolyphosphate, and 95~105 parts of water.

[0022] The chemical composition of the transparent dry granules, by mass percentage, includes: SiO2 56.5~57.7%, Al2O3 7.3~7.8%, CaO 11.5~13.0%, K2O 6.0~7.0%, BaO 3.0~4.0%, ZnO 10.5~12.0%, SrO 0.5~1.0%, with the balance being oxide impurities and / or loss on ignition, each with a weight percentage ≤0.5%. In step S5, 50~250 mesh transparent dry granules are applied using a dry granulator at a rate of 640~660 g / m³. 2 The initial melting point of the transparent dry granules is 842~852℃, and the softening point is 1006~1016℃.

[0023] The base glaze is prepared by ball milling the base glaze raw materials according to weight proportions and adding glaze-forming auxiliary materials. The base glaze raw materials, by weight proportions, include: 320 parts of first glaze powder and 45.5 parts of zirconium silicate. The glaze-forming auxiliary materials for the base glaze consist of 0.7-0.9 parts of methylcellulose, 1.1-1.3 parts of sodium tripolyphosphate, and 150-160 parts of water, by weight proportions. The application rate of the base glaze is 360-380 g / m³. 2 The chemical composition of the first glaze powder, by weight percentage, includes: SiO2 58.5~63.0%, Al2O3 7.0~8.0%, CaO 7.0~8.0%, K2O 2.0~3.0%, Na2O 0.5~1.0%, ZrO2 15.5~17.0%, with the balance being oxide impurities and / or loss on ignition, each with a weight percentage ≤0.5%.

[0024] The raw material chemical composition of the billet, by weight percentage, includes: SiO2 66.00~68.00%, Al2O3 19.50~21.00%, Fe2O3 0.50~0.65%, CaO 0.45~0.55%, MgO 0.8~1.0%, K2O 3.00~4.00%, Na2O 2.00~3.00%, with the balance being oxide impurities and / or loss on ignition, each with a weight percentage ≤0.5%.

[0025] This application provides dry-granule polished glazed tiles, which are prepared by any of the aforementioned methods for preparing dry-granule polished glazed tiles.

[0026] The technical solution of the present invention will be further described in detail below with reference to specific embodiments or comparative examples. In the following embodiments and comparative examples, the raw materials and reagents, unless otherwise specified, are all obtained commercially available, and the same batch of raw materials or reagents are used in the embodiments and comparative examples. The preparation methods without special conditions are all prepared by conventional and well-known preparation methods.

[0027] In the specific embodiments, Examples 1 to 5 and Comparative Examples 2 to 7 all used the same raw material for the billet. The chemical composition of the raw material for the billet, by weight percentage, was: SiO2 67.00%, Al2O3 20.13%, Fe2O3 0.62%, CaO 0.50%, MgO 0.82%, K2O 3.69%, Na2O 2.54%, with the balance being oxide impurities and loss on ignition with a weight percentage of ≤0.5% for each individual item.

[0028] In the specific embodiment, methyl refers to methylcellulose, and trimer refers to sodium tripolyphosphate; CVD00939 adhesive is a ceramic adhesive produced by Torrecia (Suzhou) Ceramic Glaze Colorant Co., Ltd. The weight percentage of the oxide chemical composition of the first glaze powder, the second glaze powder, and the transparent dry granules in the specific embodiment is shown in Table 1.

[0029] Table 1 In the specific embodiments, the initial melting point, softening point, and initial sintering temperature of the first glaze powder, the second glaze powder, and the transparent dry granules are shown in Table 2.

[0030] Table 2 Example 1 (1) Prepare ceramic blanks, press the ceramic blanks, and dry them to obtain the blank layer; (2) Weigh 320g of first glaze powder, 45.5g of zirconium silicate, 0.8g of methyl, 1.2g of trimer and 152g of water, and ball mill for 20 minutes to obtain the base glaze for later use.

[0031] (3) Weigh 200g of second glaze powder, 15g of alumina, 0.8g of methyl, 0.6g of trimer and 100g of water, ball mill for 20min and then add CVD00939 glue to adjust the specific gravity to 1.15 to obtain the first medium glaze for later use. (4) Weigh 200g of the second glaze powder, 0.8g of methyl, 0.6g of trimer and 100g of water, ball mill for 20min and then add CVD00939 glue to adjust the specific gravity to 1.05 to obtain the second medium glaze for later use. (5) Apply a base glaze to the surface of the body layer to obtain a base glaze layer; the amount of base glaze applied is 370 g / m 2 .

[0032] (6) Inkjet printing is performed on the surface of the base glaze layer to obtain an inkjet printed layer; (7) Spray the first medium glaze onto the surface of the inkjet printing layer, with a glaze application rate of 190 g / m. 2 The first glaze layer is obtained; (8) Apply transparent dry granules (50-250 mesh) to the surface of the first glaze layer using a dry granule applicator. The application rate of the dry granules is 650 g / m². 2 A second glaze layer is obtained; (9) Spray a second medium glaze onto the surface of the second glaze layer, with a spraying amount of 160 g / m. 2 The third glaze layer is obtained; (10) The glazed body is fired (firing temperature is 1200℃, firing cycle is 65min) and polished to obtain dry granule glazed tile.

[0033] Example 2 (1) Prepare ceramic blanks, press the ceramic blanks, and dry them to obtain the blank layer; (2) Weigh 320g of first glaze powder, 45.5g of zirconium silicate, 0.8g of methyl, 1.2g of trimer and 152g of water, and ball mill for 20 minutes to obtain the base glaze for later use.

[0034] (3) Weigh 200g of second glaze powder, 15g of alumina, 0.8g of methyl, 0.6g of trimer and 100g of water, ball mill for 20min and then add CVD00939 glue to adjust the specific gravity to 1.15 to obtain the first medium glaze for later use. (4) Weigh 200g of the second glaze powder, 0.8g of methyl, 0.6g of trimer and 100g of water, ball mill for 20min and then add CVD00939 glue to adjust the specific gravity to 1.05 to obtain the second medium glaze for later use. (5) Apply a base glaze to the surface of the body layer to obtain a base glaze layer; the amount of base glaze applied is 370 g / m 2 .

[0035] (6) Inkjet printing is performed on the surface of the base glaze layer to obtain an inkjet printed layer; (7) Spray a first medium glaze onto the surface of the inkjet printing layer, with a glaze application rate of 195 g / m. 2 The first glaze layer is obtained; (8) Apply transparent dry granules (50-250 mesh) to the surface of the first glaze layer using a dry granule applicator. The application rate of the dry granules is 650 g / m². 2 A second glaze layer is obtained; (9) Spray a second medium glaze onto the surface of the second glaze layer, with a spraying amount of 165 g / m. 2 The third glaze layer is obtained; (10) The glazed body is fired (firing temperature is 1200℃, firing cycle is 65min) and polished to obtain dry granule glazed tile.

[0036] Example 3 (1) Prepare ceramic blanks, press the ceramic blanks, and dry them to obtain the blank layer; (2) Weigh 320g of first glaze powder, 45.5g of zirconium silicate, 0.8g of methyl, 1.2g of trimer and 152g of water, and ball mill for 20 minutes to obtain the base glaze for later use.

[0037] (3) Weigh 200g of second glaze powder, 15g of alumina, 0.8g of methyl, 0.6g of trimer and 100g of water, ball mill for 20min and then add CVD00939 glue to adjust the specific gravity to 1.15g / ml to prepare the first medium glaze for later use. (4) Weigh 200g of the second glaze powder, 0.8g of methyl, 0.6g of trimer and 100g of water, ball mill for 20min and then add CVD00939 glue to adjust the specific gravity to 1.05g / ml to prepare the second medium glaze for later use. (5) Apply a base glaze to the surface of the body layer to obtain a base glaze layer; the amount of base glaze applied is 370 g / m 2 .

[0038] (6) Inkjet printing is performed on the surface of the base glaze layer to obtain an inkjet printed layer; (7) Spray the first medium glaze onto the surface of the inkjet printing layer, with a glaze application rate of 200 g / m. 2 The first glaze layer is obtained; (8) Apply transparent dry granules (50-250 mesh) to the surface of the first glaze layer using a dry granule applicator. The application rate of the dry granules is 650 g / m². 2 A second glaze layer is obtained; (9) Spray a second medium glaze onto the surface of the second glaze layer, with a spraying amount of 170 g / m. 2 The third glaze layer is obtained; (10) The glazed body is fired (firing temperature is 1200℃, firing cycle is 65min) and polished to obtain dry granule glazed tile.

[0039] Example 4 (1) Prepare ceramic blanks, press the ceramic blanks, and dry them to obtain the blank layer; (2) Weigh 320g of first glaze powder, 45.5g of zirconium silicate, 0.8g of methyl, 1.2g of trimer and 152g of water, and ball mill for 20 minutes to obtain the base glaze for later use.

[0040] (3) Weigh 200g of the second glaze powder, 15g of alumina, 0.8g of methyl, 0.6g of trimer and 100g of water, ball mill for 20min and then add CVD00939 glue to adjust the specific gravity to 1.14g / ml to prepare the first medium glaze for later use. (4) Weigh 200g of the second glaze powder, 0.8g of methyl, 0.6g of trimer and 100g of water, ball mill for 20min and then add CVD00939 glue to adjust the specific gravity to 1.04g / ml to prepare the second medium glaze for later use. (5) Apply a base glaze to the surface of the body layer to obtain a base glaze layer; the amount of base glaze applied is 370 g / m 2 .

[0041] (6) Inkjet printing is performed on the surface of the base glaze layer to obtain an inkjet printed layer; (7) Spray the first medium glaze onto the surface of the inkjet printing layer, with a glaze application rate of 200 g / m. 2 The first glaze layer is obtained; (8) Apply transparent dry granules (50-250 mesh) to the surface of the first glaze layer using a dry granule applicator. The application rate of the dry granules is 650 g / m². 2 A second glaze layer is obtained; (9) Spray a second medium glaze onto the surface of the second glaze layer, with a spraying amount of 170 g / m. 2 The third glaze layer is obtained; (10) The glazed body is fired (firing temperature is 1185℃, firing cycle is 63.55min) and polished to obtain dry granule glazed tile.

[0042] Example 5 (1) Prepare ceramic blanks, press the ceramic blanks, and dry them to obtain the blank layer; (2) Weigh 320g of first glaze powder, 45.5g of zirconium silicate, 0.8g of methyl, 1.2g of trimer and 152g of water, and ball mill for 20 minutes to obtain the base glaze for later use.

[0043] (3) Weigh 200g of second glaze powder, 15g of alumina, 0.8g of methyl, 0.6g of trimer and 100g of water, ball mill for 20min and then add CVD00939 glue to adjust the specific gravity to 1.16g / ml to prepare the first medium glaze for later use. (4) Weigh 200g of the second glaze powder, 0.8g of methyl, 0.6g of trimer and 100g of water, ball mill for 20min and then add CVD00939 glue to adjust the specific gravity to 1.06g / ml to prepare the second medium glaze for later use. (5) Apply a base glaze to the surface of the body layer to obtain a base glaze layer; the amount of base glaze applied is 370 g / m 2 .

[0044] (6) Inkjet printing is performed on the surface of the base glaze layer to obtain an inkjet printed layer; (7) Spray the first medium glaze onto the surface of the inkjet printing layer, with a glaze application rate of 200 g / m. 2 The first glaze layer is obtained; (8) Apply transparent dry granules (50-250 mesh) to the surface of the first glaze layer using a dry granule applicator. The application rate of the dry granules is 650 g / m². 2 A second glaze layer is obtained; (9) Spray a second medium glaze onto the surface of the second glaze layer, with a spraying amount of 170 g / m. 2 The third glaze layer is obtained; (10) The glazed body is fired (firing temperature is 1185℃, firing cycle is 63.55min) and polished to obtain dry granule glazed tile.

[0045] Comparative Example 1 Dry-granulated polished ceramic tiles that are commonly purchased on the market.

[0046] Comparative Example 2 This comparative example uses the same parameters and preparation process as Example 2, the only difference being that the first glaze powder used is the conventionally produced 1096B surface glaze powder, with an initial melting point of 1086℃ and a softening point of 1136℃.

[0047] Comparative Example 3 This comparative example uses the same parameters and preparation process as Example 2, the only difference being that the second glaze powder uses conventionally produced polishing glaze powder numbered 2001.

[0048] Comparative Example 4 (1) Prepare ceramic blanks, press the ceramic blanks, and dry them to obtain the blank layer; (2) Weigh 320g of first glaze powder, 45.5g of zirconium silicate, 0.8g of methyl, 1.2g of trimer and 152g of water, and ball mill for 20 minutes to obtain the base glaze for later use.

[0049] (3) Weigh 200g of second glaze powder, 15g of alumina, 0.8g of methyl, 0.6g of trimer and 100g of water, ball mill for 20min and then add CVD00939 glue to adjust the specific gravity to 1.15g / ml to prepare the first medium glaze for later use. (4) Weigh 200g of the second glaze powder, 0.8g of methyl, 0.6g of trimer and 100g of water, ball mill for 20min and then add CVD00939 glue to adjust the specific gravity to 1.05g / ml to prepare the second medium glaze for later use. (5) Apply a base glaze to the surface of the body layer to obtain a base glaze layer; the amount of base glaze applied is 370 g / m 2 .

[0050] (6) Inkjet printing is performed on the surface of the base glaze layer to obtain an inkjet printed layer; (7) Spray a first medium glaze onto the surface of the inkjet printing layer, with a glaze application rate of 185 g / m. 2 The first glaze layer is obtained; (8) Apply transparent dry granules (50-250 mesh) to the surface of the first glaze layer using a dry granule applicator. The application rate of the dry granules is 650 g / m². 2 A second glaze layer is obtained; (9) Spray a second medium glaze onto the surface of the second glaze layer, with a spraying amount of 155 g / m. 2 The third glaze layer is obtained; (10) The glazed body is fired (firing temperature is 1200℃, firing cycle is 65min) and polished to obtain dry granule glazed tile.

[0051] Comparative Example 5 (1) Prepare ceramic blanks, press the ceramic blanks, and dry them to obtain the blank layer; (2) Weigh 320g of first glaze powder, 45.5g of zirconium silicate, 0.8g of methyl, 1.2g of trimer and 152g of water, and ball mill for 20 minutes to obtain the base glaze for later use.

[0052] (3) Weigh 200g of second glaze powder, 15g of alumina, 0.8g of methyl, 0.6g of trimer and 100g of water, ball mill for 20min and then add CVD00939 glue to adjust the specific gravity to 1.15g / ml to prepare the first medium glaze for later use. (4) Weigh 200g of the second glaze powder, 0.8g of methyl, 0.6g of trimer and 100g of water, ball mill for 20min and then add CVD00939 glue to adjust the specific gravity to 1.05g / ml to prepare the second medium glaze for later use. (5) Apply a base glaze to the surface of the body layer to obtain a base glaze layer; the amount of base glaze applied is 370 g / m 2 .

[0053] (6) Inkjet printing is performed on the surface of the base glaze layer to obtain an inkjet printed layer; (7) Spray a first medium glaze onto the surface of the inkjet printing layer, with a glaze application rate of 205 g / m. 2 The first glaze layer is obtained; (8) Apply transparent dry granules (50-250 mesh) to the surface of the first glaze layer using a dry granule applicator. The application rate of the dry granules is 650 g / m². 2 A second glaze layer is obtained; (9) Spray a second medium glaze onto the surface of the second glaze layer, with a spraying amount of 175 g / m. 2 The third glaze layer is obtained; (10) The glazed body is fired (firing temperature is 1200℃, firing cycle is 65min) and polished to obtain dry granule glazed tile.

[0054] Comparative Example 6 (1) Prepare ceramic blanks, press the ceramic blanks, and dry them to obtain the blank layer; (2) Weigh 320g of first glaze powder, 45.5g of zirconium silicate, 0.8g of methyl, 1.2g of trimer and 152g of water, and ball mill for 20 minutes to obtain the base glaze for later use.

[0055] (3) Weigh 200g of the second glaze powder, 15g of alumina, 0.8g of methyl, 0.6g of trimer and 100g of water, ball mill for 20min and then add CVD00939 glue to adjust the specific gravity to 1.13g / ml to prepare the first medium glaze for later use. (4) Weigh 200g of the second glaze powder, 0.8g of methyl, 0.6g of trimer and 100g of water, ball mill for 20min and then add CVD00939 glue to adjust the specific gravity to 1.03g / ml to prepare the second medium glaze for later use. (5) Apply a base glaze to the surface of the body layer to obtain a base glaze layer; the amount of base glaze applied is 370 g / m 2 .

[0056] (6) Inkjet printing is performed on the surface of the base glaze layer to obtain an inkjet printed layer; (7) Spray a first medium glaze onto the surface of the inkjet printing layer, with a glaze application rate of 185 g / m. 2 The first glaze layer is obtained; (8) Apply transparent dry granules (50-250 mesh) to the surface of the first glaze layer using a dry granule applicator. The application rate of the dry granules is 650 g / m². 2 A second glaze layer is obtained; (9) Spray a second medium glaze onto the surface of the second glaze layer, with a spraying amount of 155 g / m. 2 The third glaze layer is obtained; (10) The glazed body is fired (firing temperature is 1200℃, firing cycle is 65min) and polished to obtain dry granule glazed tile.

[0057] Comparative Example 7 (1) Prepare ceramic blanks, press the ceramic blanks, and dry them to obtain the blank layer; (2) Weigh 320g of first glaze powder, 45.5g of zirconium silicate, 0.8g of methyl, 1.2g of trimer and 152g of water, and ball mill for 20 minutes to obtain the base glaze for later use.

[0058] (3) Weigh 200g of the second glaze powder, 15g of alumina, 0.8g of methyl, 0.6g of trimer and 100g of water, ball mill for 20min and then add CVD00939 glue to adjust the specific gravity to 1.17g / ml to prepare the first medium glaze for later use. (4) Weigh 200g of the second glaze powder, 0.8g of methyl, 0.6g of trimer and 100g of water, ball mill for 20min and then add CVD00939 glue to adjust the specific gravity to 1.07g / ml to prepare the second medium glaze for later use. (5) Apply a base glaze to the surface of the body layer to obtain a base glaze layer; the amount of base glaze applied is 370 g / m 2 .

[0059] (6) Inkjet printing is performed on the surface of the base glaze layer to obtain an inkjet printed layer; (7) Spray a first medium glaze onto the surface of the inkjet printing layer, with a glaze application rate of 185 g / m. 2 The first glaze layer is obtained; (8) Apply transparent dry granules (50-250 mesh) to the surface of the first glaze layer using a dry granule applicator. The application rate of the dry granules is 650 g / m². 2 A second glaze layer is obtained; (9) Spray a second medium glaze onto the surface of the second glaze layer, with a spraying amount of 155 g / m. 2 The third glaze layer is obtained; (10) The glazed body is fired (firing temperature is 1200℃, firing cycle is 65min) and polished to obtain dry granule glazed tile.

[0060] Performance testing The glaze effect of the dry-granule polished glazed tiles with high wear resistance and stain resistance and few glaze pores prepared in Examples 1-5 and Comparative Examples 1-7 was observed, and their performance parameters were tested according to conventional wear resistance testing methods in the ceramics field. The testing methods are as follows: Glaze bubble, abrasion resistance and stain resistance testing: The various properties of the glaze surface of the product were tested using the test methods in Appendix G of GB / T4100-2015 "Ceramic Tiles" for dry-pressed ceramic tiles (E≤0.5%BIa class). The glaze bubble assessment uses the surface quality evaluation in this standard, which states that at least 95% of the main areas of the tile are free of obvious defects, which is considered acceptable.

[0061] Abrasion resistance is evaluated by placing abrasive media on the glaze surface and rotating it, and then comparing the worn sample with an unworn sample. Higher grades and rotation speeds indicate better abrasion resistance.

[0062] The stain resistance test involves contacting the test solution and stain agent with the front of the brick surface for a certain period of time, then cleaning the brick surface according to the prescribed cleaning method, and observing the visible changes on the brick surface to evaluate the stain resistance of the brick. The higher the grade, the better the stain resistance.

[0063] The test results of Examples 1-5 and Comparative Examples 1-7 are shown in Table 3.

[0064] Table 3 As can be seen from the above data, when the specific gravity of the first medium glaze was adjusted to within the range of 1.15±0.01g / ml and the specific gravity of the second medium glaze was adjusted to within the range of 1.05±0.01 in Examples 1 to 3, the dry granule polished glazed tiles prepared had fewer vent holes on the glaze surface, no obvious bubbles on the glaze surface, wear resistance reaching level 4 (above 2100 revolutions), and stain resistance reaching level 5. Among them, in Example 2, when the specific gravity of the first medium glaze was 1.15g / ml and the specific gravity of the second medium glaze was 1.05, all performances reached the optimal level.

[0065] Compared with Examples 3 to 5, when the amount of the first medium glaze applied is 190-200 g / m³ 2 The spraying amount of the second medium glaze is 160~170g / m². 2 When adjusted within the specified range, the prepared dry-granule polished glazed tiles have fewer vent holes in the glaze, no obvious bubbles in the glaze, wear resistance reaches level 4 (above 2100 revolutions), and stain resistance reaches level 5.

[0066] As can be seen from Comparative Example 1, commercially available dry-granule polished ceramic tiles have bubbles on the glaze surface and are of poor wear resistance.

[0067] As can be seen from the comparison between Example 2 and Comparative Example 2, when the base glaze layer uses a conventional top glaze, there are obvious bubbles on the glaze surface, which has no significant impact on wear resistance, but significantly reduces the stain resistance.

[0068] As can be seen from the comparison of Example 2 and Comparative Example 3, when the second glaze powder in the first medium glaze and the second medium glaze is replaced with conventional polishing glaze powder, there are obvious bubbles on the glaze surface, and the wear resistance and stain resistance are significantly reduced.

[0069] Comparing Example 2 and Comparative Examples 4-5, it can be seen that when the amount of the first medium glaze and the amount of the second medium glaze are lower than the range of the scheme, there are obvious bubbles on the glaze surface and the stain resistance decreases. When the amount of the first medium glaze and the amount of the second medium glaze are higher than the range of the scheme, there are no obvious bubbles on the glaze surface, but the wear resistance and stain resistance decrease.

[0070] Comparing Example 2 and Comparative Examples 6-7, it can be seen that when the specific gravity of the first medium glaze and the second medium glaze is lower than the specified range, there are obvious bubbles on the glaze surface, and the stain resistance decreases; when the specific gravity of the first medium glaze and the second medium glaze is higher than the specified range, there are no obvious bubbles on the glaze surface, but the wear resistance and stain resistance decrease.

[0071] The above description is merely a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.

Claims

1. A method for preparing dry-granulated polished glazed tiles, characterized in that, Includes the following steps: S1. Prepare a green body and dry the green body to obtain a green body layer; S2. Apply a base glaze to the surface of the body layer. The initial melting point of the base glaze is 1068~1076℃ and the softening point is 1170~1178℃ to obtain the base glaze layer. S3. Inkjet printing is performed on the surface of the base glaze layer to obtain an inkjet printed layer; S4. Apply a first medium glaze to the surface of the inkjet printing layer to obtain a first glaze layer; S5. Apply transparent dry particles to the surface of the first glaze layer to obtain the second glaze layer; S6. Apply a second medium glaze to the surface of the second glaze layer to obtain a third glaze layer; S7. Firing in a kiln at a temperature of 1185~1200℃ for a firing cycle of 63.55~65.00 min, followed by polishing of the tile surface.

2. The method for preparing dry-granulated glazed tiles as described in claim 1, characterized in that, In steps S4 / S6, the first / second medium glaze is adjusted by adding ceramic adhesive to adjust the specific gravity of the glaze slurry. In step S4, the first raw material is weighed according to its weight proportions, and then glaze-forming auxiliary materials are added and ball-milled to obtain the first medium glaze with a specific gravity of 1.15±0.01 g / ml. The first raw material, according to its weight proportions, includes: 195~205 parts of second glaze powder and 13~17 parts of alumina. The spraying amount of the first medium glaze is 190~200 g / ml. 2 ; In step S6, the second raw material is weighed according to the weight parts, and then glaze-forming auxiliary materials are added and ball-milled to obtain the second medium glaze with a specific gravity of 1.05±0.

01. The second raw material includes, by weight, 195~205 parts of second glaze powder, and the spraying amount of the second medium glaze is 160~170g / m³. 2 ; The chemical composition of the second glaze powder, by weight percentage, includes: SiO2 53.5 ~ 56.0%, Al2O3 11.5 ~ 13.0%, CaO 21 ~ 23%, MgO 1.0 ~ 2.0%, K2O 1.95 ~ 3.0%, Na2O 3.0 ~ 4.0%, with the balance being oxide impurities and / or loss on ignition, each with a weight percentage ≤ 0.5%. The glazing additives for the first and second medium glazes are composed of 0.7 to 0.9 parts by weight of methylcellulose, 0.5 to 0.7 parts by weight of sodium tripolyphosphate and 95 to 105 parts by weight of water.

3. The method for preparing dry-granule polished glazed tiles as described in claim 2, characterized in that, The second glaze powder has an initial melting point of 1095~1105℃ and a softening point of 1147~1157℃; the transparent dry granules have an initial melting point of 842~852℃ and a softening point of 1006~1016℃.

4. The method for preparing dry-granule polished glazed tiles as described in claim 2 or 3, characterized in that, The chemical composition of the transparent dry granules, by mass percentage, includes: SiO2 56.5~57.7%, Al2O3 7.3~7.8%, CaO 11.5~13.0%, K2O 6.0~7.0%, BaO 3.0~4.0%, ZnO 10.5~12.0%, SrO 0.5~1.0%, with the balance being oxide impurities and / or loss on ignition, each with a weight percentage ≤0.5%. In step S5, transparent dry granules of 50-250 mesh are applied using a dry granulator, with an application rate of 640-660 g / m³. 2 .

5. The method for preparing dry-granule polished glazed tiles as described in claim 1 or 2, characterized in that, The base glaze is obtained by ball milling the base glaze raw materials according to the weight parts and adding the glaze auxiliary materials. The base glaze raw materials include, by weight parts: 315~325 parts of first glaze powder and 45~48 parts of zirconium silicate. The chemical composition of the first glaze powder includes, by weight percentage: SiO2 58.5~63.0%, Al2O3 7.0~8.0%, CaO 7.0~8.0%, K2O 2.0~3.0%, Na2O 0.5~1.0%, ZrO2 15.5~17.0%, with the balance being oxide impurities or loss on ignition with a single content ≤0.5%. The amount of the base glaze applied is 360~380 g / m³. 2 ; The glaze-forming auxiliary materials of the base glaze are composed of 0.7-0.9 parts by weight of methylcellulose, 1.1-1.3 parts by weight of sodium tripolyphosphate and 150-160 parts by weight of water.

6. The method for preparing dry-granule polished glazed tiles as described in claim 1 or 2, characterized in that, The raw material chemical composition of the billet, by weight percentage, includes: SiO2 66.00~68.00%, Al2O3 19.50~21.00%, Fe2O3 0.50~0.65%, CaO 0.45~0.55%, MgO 0.8~1.0%, K2O 3.00~4.00%, Na2O 2.00~3.00%, with the balance being oxide impurities and / or loss on ignition, each with a weight percentage ≤0.5%.

7. Dry-granulated polished glazed tiles, characterized in that, It is prepared by any one of the preparation methods of dry granule polished glazed tiles as described in claims 1 to 6.